What can be found in scalp EEG spectrum beyond common frequency bands. EEG-fMRI study - Marecek, R; Lamos, M; Mikl, M; Barton, M; Fajkus, J; Rektor; Brazdil, M (Journal of neural engineering, 2016)
OBJECTIVE: The scalp EEG spectrum is a frequently used marker of neural activity. Commonly, the preprocessing of EEG utilizes constraints, e.g. dealing with a predefined subset of electrodes or a predefined frequency band of interest. Such treatment of the EEG spectrum neglects the fact that particular neural processes may be reflected in several frequency bands and/or several electrodes concurrently, and can overlook the complexity of the structure of the EEG spectrum. APPROACH: We showed that the EEG spectrum structure can be described by parallel factor analysis (PARAFAC), a method which blindly uncovers the spatial-temporal-spectral patterns of EEG. We used an algorithm based on variational Bayesian statistics to reveal nine patterns from the EEG of 38 healthy subjects, acquired during a semantic decision task. The patterns reflected neural activity synchronized across theta, alpha, beta and gamma bands and spread over many electrodes, as well as various EEG artifacts. MAIN RESULTS: Specifically, one of the patterns showed significant correlation with the stimuli timing. The correlation was higher when compared to commonly used models of neural activity (power fluctuations in distinct frequency band averaged across a subset of electrodes) and we found significantly correlated hemodynamic fluctuations in simultaneously acquired fMRI data in regions known to be involved in speech processing. Further, we show that the pattern also occurs in EEG data which were acquired outside the MR machine. Two other patterns reflected brain rhythms linked to the attentional and basal ganglia large scale networks. The other patterns were related to various EEG artifacts. SIGNIFICANCE: These results show that PARAFAC blindly identifies neural activity in the EEG spectrum and that it naturally handles the correlations among frequency bands and electrodes. We conclude that PARAFAC seems to be a powerful tool for analysis of the EEG spectrum and might bring novel insight to the relationships between EEG activity and brain hemodynamics.
Keywords: Young Adult; Electroencephalography; Male; Oxygen; Psychomotor Performance; Cerebrovascular Circulation; magnetická rezonanční tomografie; mladý dospělý; Bayes Theorem; Nerve Net; psychomotorický výkon; mozkový krevní oběh; artefakty; elektroencefalografie; Adult; dospělí; Scalp; mužské pohlaví; algoritmy; Multimodal Imaging; faktorová analýza statistická; Hemodynamics; Factor Analysis, Statistical; lidé; kyslík; ženské pohlaví; multimodální zobrazování; Humans; nervová síť; Algorithms; Bayesova věta; Artifacts; Magnetic Resonance Imaging; hemodynamika; skalp; Female